Tanshinone IIA Inhibits Epithelial-to-Mesenchymal Transition Through Hindering β-Arrestin1 Mediated β-Catenin Signaling Pathway in Colorectal Cancer - Song, Qing; Yang, Liu; Han, Zhifen; Wu, Xinnan; Li, Ruixiao; Zhou, Lihong; Liu, Ningning; Sui, Hua; Cai, Jianfeng; Wang, Yan; Ji, Qing; Li, Qi (Frontiers in Pharmacology, 2020)
Tanshinone IIA (Tan IIA) is a major active ingredient extracted from Salvia miltiorrhiza, which has been proved to be able to inhibit metastasis of various cancers including colorectal cancer (CRC). However, the mechanisms of anti-metastatic effect of Tan IIA on CRC are not well explored. A number of studies indicate that epithelial-to-mesenchymal transition (EMT) plays an important role in CRC metastasis, and our previous studies demonstrate that β-arrestin1could regulate EMT in CRC partly through β-catenin signaling pathway. In this work, we investigate whether Tan IIA could regulate EMT in CRC through β-arrestin1-mediated β-catenin signaling pathway both in vivo and in vitro. Our results showed that Tan IIA inhibited lung metastases of CRC cells in vivo and extended the survival time of mice with CRC. In vitro, Tan IIA increased the expression of E-cadherin, decreased the expression of Snail, N-cadherin and Vimentin, thus suppressed EMT and the migratory ability of CRC cells. Further study found that the mechanism of action of Tan IIA in regulating EMT and metastasis is associated with the suppression of β-arrestin1 expression, resulting in the increase of GSK-3β expression, reduction of β-catenin nuclear localization, thereby decreased the activity of β-catenin signaling pathway. Our data revealed a new mechanism of Tan IIA on the suppression of EMT and metastasis in CRC via β-arrestin1-mediated β-catenin signaling pathway and provided support for using Tan IIA as anti-metastatic agents in CRC.